Unproven stem cell–based interventions and achieving a compromise policy among the multiple stakeholders. Issue 1 (December 2015) - Matthews, Kirstin; Iltis, Ana
Abstract Background In 2004, patient advocate groups were major players in helping pass and implement significant public policy and funding initiatives in stem cells and regenerative medicine. In the following years, advocates were also actively engaged in Washington DC, encouraging policy makers to broaden embryonic stem cell research funding, which was ultimately passed after President Barack Obama came into office. Many advocates did this because they were told stem cell research would lead to cures. After waiting more than 10 years, many of these same patients are now approaching clinics around the world offering experimental stem cell-based interventions instead of waiting for scientists in the US to complete clinical trials. How did the same groups who were once (and often still are) the strongest supporters of stem cell research become stem cell tourists? And how can scientists, clinicians, and regulators work to bring stem cell patients back home to the US and into the clinical trial process? Discussion In this paper, we argue that the continued marketing and use of experimental stem cell-based interventions is problematic and unsustainable. Central problems include the lack of patient protection, US liability standards, regulation of clinical sites, and clinician licensing. These interventions have insufficient evidence of safety and efficacy; patients may be wasting money and time, and they may be forgoing other opportunities for an intervention that has not been shown to be safe and effective. Current practices do not contribute to scientific progress because the data from the procedures are unsuitable for follow-up research to measure outcomes. In addition, there is no assurance for patients that they are receiving the interventions promised or of what dosage they are receiving. Furthermore, there is inconsistent or non-existent follow-up care. Public policy should be developed to correct the current situation. Conclusion The current landscape of stem cell tourism should prompt a re-evaluation of current approaches to study cell-based interventions with respect to the design, initiation, and conduct of US clinical trials. Stakeholders, including scientists, clinicians, regulators and patient advocates, need to work together to find a compromise to keep patients in the US and within the clinical trial process. Using HIV/AIDS and breast cancer advocate cases as examples, we identify key priorities and goals for this policy effort.